2018
DOI: 10.1186/s13256-018-1807-8
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma presenting as spinal cord compression in Native Americans with controlled hepatitis C: two case reports

Abstract: BackgroundHepatocellular carcinoma is a common malignancy in Asia. It is associated with chronic hepatitis B virus or hepatitis C virus infection and alcoholic hepatitis. Commonly, the tumor metastasizes to the lungs, regional lymph nodes, and bone. Recently, the incidence of metastatic spinal cord compression caused by primary hepatocellular carcinoma has been reported more frequently due to improved diagnosis and therapeutic modalities. The presentation of primary hepatocellular carcinoma with spinal cord co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Spinal cord compression as the initial presentation of HCC is exceedingly rare. In a case report by Liaukovich, two patients of age 64 years and 70 years, male, initially presented with the symptoms of spinal cord compression due to metastasis of HCC [ 5 ]. In a review of a series of 600 patients with spinal cord compression, HCC has been reported in less than 2% of cases, making it an infrequent feature of HCC [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord compression as the initial presentation of HCC is exceedingly rare. In a case report by Liaukovich, two patients of age 64 years and 70 years, male, initially presented with the symptoms of spinal cord compression due to metastasis of HCC [ 5 ]. In a review of a series of 600 patients with spinal cord compression, HCC has been reported in less than 2% of cases, making it an infrequent feature of HCC [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have reported that MSCC could be the initial presentation of malignancy up to 20%, [3][4][5] and it can occur in any cancer type. [10][11][12] Regardless of whether the site of the primary cancer is known or not, surgery does play a role in spinal metastases management because MSCC is an oncological emergency that necessitates immediate surgical intervention. According to a recent review, an integrated multidisciplinary approach is needed for the management of spinal metastases due to its complexity.…”
Section: Discussionmentioning
confidence: 99%